The relationship between academic dishonesty and achievement motivation among undergraduate students at two selected kulliyyahs of IIUM - Zubir Asadi Mohamad (Kulliyyah of Education, International Islamic University Malaysia, 2015)
The purpose of this investigation is to examine the connection concerning academic dishonesty and achievement motivation among year two, year three and year four undergraduate students at the two selected kulliyyah of International Islamic University Malaysia (IIUM). Basically, the study used a quantitative method with 380 respondents consisted of 180 male students and 200 female students who were selected via a purposive sampling procedure from an entire population of 7462 respondents from two diverse Kulliyyah in IIUM. All data of this study were compiled by consuming two instruments; the Academic Integrity Students Survey developed by McCabe (2000) and Motivated Strategies for Learning Questionnaire Subscales (MLSQ) expanded by Pintrich (1990).Descriptive analysis such as percentage, standard deviation, mean, one-way Analysis of Variance (ANOVA) and independent sample t-test were applied in analyzing the data which were gathered through the mentioned instruments. The overall findings of this investigation exposed and revealed that there were significant differences concerning the level of academic dishonesty, gender, and kulliyyah. However, in connection with level of study there was no statistically significant difference found in academic dishonesty. Besides, on the issue of achievement motivation among respondents in both kulliyyahs, there were no statistically significant difference found by gender, kulliyyah and levels of study. In general, both intrinsic motivation and extrinsic motivation predominantly influenced the academic dishonesty among students at International Islamic university of Malaysia (IIUM).